Determination of Chromium(III) in Real Samples by Flame Atomic Absorption Spectrometry with Cloud Point Extraction Using Tergitol TMN-6 - Meng, Lifen; Ning, Jinyan; Zhao, Jiao; Bi, Li (Asian Journal of Chemistry, 2014)
A rapid and selective cloud point extraction based on tergitol TMN-6 has been used for determination of chromium ion. 8-Hydroxyquinoline (oxine) was used as a selective complexing agent to form stable Cr-oxine complex which can be extracted with TMN-6 at a short time and its determination using flame atomic absorption spectrometry (FAAS). Several variables such as sample pH, concentration of oxine and salt, equilibration temperature and time, the effect of foreign ions were evaluated in order to enhance sensitivity of the method. Under the optimum conditions, the limit of detection (LOD) was 2.9 μg L-1 and relative standard deviation (RSD %) was 4.2 % (n = 11). The cloud point extraction method has been shown to be a potentially useful methodology for the preconcentration of the target analytes, with a preconcentration factor of 20. The high recoveries of the spiked Cr(III) ions were obtained in the range 90-108 %. This method was compared with cloud point extraction (using Triton X-114) and liquid-liquid microextraction (using ionic liquid).